Pengaruh Daya Tarik Wisata Terhadap Keputusan Berkunjung dan Kepuasan Sebagai Variabel Mediasi di Jasmine Park, Cisauk, Kabupaten Tangerang, Provinsi Banten - Nurbaeti Nurbaeti; Anita Swantari; Heny Ratnaningtyas; Dwi Rifki Junandar; Jesica Septiani Eka Putri (Jurnal Ilmiah Pariwisata, 2026)
This study aims to analyze the effect of tourist attraction on visitor satisfaction and revisit intention at Jasmine Park, Cisauk, Tangerang Regency, Banten Province. It also examines the role of visitor satisfaction as a mediator in the relationship between tourist attraction and revisit intention. The research method used is Structural Equation Modeling (SEM) with SmartPLS 3.2.8, involving 150 respondents who were visitors to Jasmine Park. Data were collected through questionnaires distributed to visitors who had previously visited the park. The results show that tourist attraction has a positive and significant effect on both visitor satisfaction and revisit intention. In addition, visitor satisfaction is proven to mediate the relationship between tourist attraction and revisit intention. A unique tourist attraction that meets visitors’ expectations contributes to higher satisfaction, which in turn influences visitors’ intention to revisit. The conclusion of this study is that strong tourist attractions enhance visitor satisfaction, which ultimately increases revisit intention. It is recommended that managers continuously improve facilities and services, visitors provide feedback, and local governments support the development of the tourism sector to further enhance tourist attractions in the area. Keywords: daya tarik wisata, kepuasan pengunjung, keputusan berkunjung